2016
DOI: 10.1364/oe.24.004010
|View full text |Cite
|
Sign up to set email alerts
|

Backward terahertz radiation from intense laser-solid interactions

Abstract: We report a systematic study on backward terahertz (THz) radiation generation from laser-solid interactions by changing a variety of laser/plasma parameters. We demonstrate a high-energy (with an energy flux density reaching 80 μJ/sr), broadband (>10 THz) plasma-based radiation source. The radiation energy is mainly distributed either in the >10 THz or <3 THz regions. A radial surface current formed by the lateral transport of low-energy electrons (LEE) is believed to be responsible for the radiation in the hi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
17
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(17 citation statements)
references
References 25 publications
0
17
0
Order By: Relevance
“…Unlike terahertz emission from the target front surface where the NIR laser pulse interacts with the solid foil, the generation of coherent terahertz radiation from the rear surface is different. In the case of emission from the target front surface, there are a multitude of physical processes responsible for terahertz generation from the laser-plasma interaction region [23][24][25][26][27][28] which are directly dependent on the incident laser parameters (polarization, ASE contrast, pulse duration, intensity) and target material etc. However, in the case of emission from the rear surface [7,8,[29][30][31][32][33][34] the THz dynamics has to depend on the hot electrons which are generated at the front surface during the interaction of laser pulse with the foil and gain energy and accelerated back to the target ballistically, travel through the target and exit the rear surface.…”
Section: Thz Generation At the Target Rear Surfacementioning
confidence: 99%
“…Unlike terahertz emission from the target front surface where the NIR laser pulse interacts with the solid foil, the generation of coherent terahertz radiation from the rear surface is different. In the case of emission from the target front surface, there are a multitude of physical processes responsible for terahertz generation from the laser-plasma interaction region [23][24][25][26][27][28] which are directly dependent on the incident laser parameters (polarization, ASE contrast, pulse duration, intensity) and target material etc. However, in the case of emission from the rear surface [7,8,[29][30][31][32][33][34] the THz dynamics has to depend on the hot electrons which are generated at the front surface during the interaction of laser pulse with the foil and gain energy and accelerated back to the target ballistically, travel through the target and exit the rear surface.…”
Section: Thz Generation At the Target Rear Surfacementioning
confidence: 99%
“…Two-dimensional PIC simulations show that there usually exists two kinds of lateral transient currents with different characteristics near the target surface [33]. One is formed by the directional surface fast electron (SFE) beam due to the confinement of the quasistatic magnetic and electric fields (Current I) [34].…”
Section: Target Surface Transient Currentmentioning
confidence: 99%
“…The other is the radial surface current formed by the lateral electron transport in low-density plasmas (Current II). A moderate plasma density scalelength and a small incidence angle are useful to enhance the Current II [33]. In the PIC simulations, strong lateral return currents are formed by "cold" background electrons which almost cancel out the fast electron currents in the high-density region.…”
Section: Target Surface Transient Currentmentioning
confidence: 99%
See 1 more Smart Citation
“…When a solid foil is irradiated by a pump laser with intensities over 10 18 W/cm 2 , produced fast electrons pass through the front and rear surfaces of the target, which lead to coherent transition radiation (CTR) of THz pulses in backward and forward directions, respectively [19,20]. Several experimental and numerical studies have shown that the energy of fast electrons is normally on the order of ∼100 keV or ∼MeV [21][22][23], so most of the hot electrons in the low-energy end of the spectrum do not contribute to THz generation, as they cannot escape the electrostatic fields near the target bulk. Besides, a large beam divergence (∼40 • ) is typically observed in the experiments [24], which significantly suppresses conversion efficiency [20].…”
Section: Introductionmentioning
confidence: 99%